The Reliability and Validity Study of The Partner Breastfeeding Influence Scale - Emel Buldur; Nurdan Akçay Didişen (Journal of Pediatric Research)
Aim: This study aimed to assess the validity and reliability of the Partner Breastfeeding Influence Scale (PBIS) in the Turkish population. Materials and Methods: This research was carried out as a methodological descriptive cross-sectional study. The study population consisted of 301 fathers who attended a new-born outpatient clinic at a children’s hospital from July, 2018 to December, 2018. The data for this study were gathered via the Person Identification Form and the PBIS. The scale comprises five subscales and a total of 37 items. The subscales include Breastfeeding Savvy, Helping, Appreciation, Breastfeeding Presence and Responsiveness. The validity of this scale was assessed by exploratory and confirmatory factor analyses. Results: The Cronbach’s alpha correlation coefficient was determined to be 0.95 for the entire scale and between 0.75 to 0.83 for the subscales. The exploratory factor analysis accounted for 59.09% of the overall variation. The factor load values of the scale, as determined using confirmatory factor analysis, ranged from 0.28 to 0.82. Goodness of Fit Index, Normed Fit Index, Non-Normed Fit Index, and Comparative Fit Index were greater than 0.90, whereas root mean square error of approximation was less than or equal to 0.08. Conclusion: PBIS is a credible and dependable instrument applicable in Turkish culture.